PERAN KEPALA MADRASAH DALAM MENINGKATKAN MUTU PENDIDIKAN DI MI AL-IMAN BULUS KECAMATAN GEBANG KABUPATEN PURWOREJO - Gus Mundir; Aniqoh L.c.; Siti Anisatun Nafi'ah (Program Studi Pendidikan Guru Madrasah Ibtidaiyah STAINU Purworejo, 2022)
This study aims to describe (1) The role of the principal in improving the quality of education at MI Al-Iman Bulus (2) Improving the quality of education at MI Al-Iman Bulus The research method used is descriptive qualitative method. The research location is at MI Al-Iman Bulus, Gebang sub-district, Purworejo district, the data collection techniques used are interviews, observation and documentation while data analysis uses triangulation. The results showed that: 1) The role of the madrasah principal in improving the quality of education at MI Al-Iman Bulus as Educator, Manager, Leader Supervisor, Innovator, Motivator. The method used is coaching teachers and education staff through KKG, Workshop, Training, Seminar or webinars, involving all teachers and education staff in madrasa activities, placing teachers and education staff according to their diploma qualifications, setting an example of discipline by leaving early., supervise the implementation of teaching and learning, provide follow-up or solutions to teachers in need, make innovations or new breakthroughs. reward, be a role model. 2) Education at MI Al-Iman Bulus can be said to be of high quality, seen from a clear vision and mission, professional madrasa heads and teachers, a conducive madrasa environment, a broad and balanced curriculum and high community involvement in every madrasa activity.